The Politics of Islamic Education and the Independent Curriculum as an Effort to Integrate Islamic Values in the National Education System - Asdianur Hadi; Syarif Hidayat (Islamic Journal of Education, 2024)
Islamic education in Indonesia has always been in the vortex of continuously evolving policy dynamics. One of the latest policies affecting Islamic education is the Merdeka Curriculum, which offers flexibility for schools and teachers in designing more contextualized learning experiences. However, within this increasingly open system, a significant challenge arises in ensuring that Islamic values remain an inseparable part of the national education system. This study employs a qualitative method with a literature review and policy analysis approach to understand the dynamics of Islamic education politics within the context of the Merdeka Curriculum. Data were obtained from journals, academic books, government policy documents, and related research reports, which were analyzed using descriptive-qualitative analysis and political analysis to assess the extent to which Islamic education has been accommodated in the Merdeka Curriculum. The findings indicate that the Merdeka Curriculum provides a significant opportunity for Islamic education to remain relevant in contemporary times, but challenges persist, such as the lack of explicit regulations on integrating Islamic values, limited resources, and teachers' readiness to implement these concepts. Therefore, synergy between the government, educators, and Islamic educational institutions is essential to ensure that Islamic education retains a strong position within the national education system